Corporate Social Responsibility pada Masyarakat Sekitar PT. Virtue Dragon Nickel Industri di Kabupaten Konawe - Ampi, Muhamad Albain; Sutinah, Sutinah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
Natural resource extraction often causes environmental and social harm. Virtue Dragon Nickel Inc. (VDNI Inc.), a nickel processing company, is legally required to implement Corporate Social Responsibility (CSR) under Law No. 40 of 2007 on Limited Liability Companies. This study examines VDNI Inc.’s CSR implementation in Morosi and Puuruy villages, Morosi District, Konawe Regency, using a qualitative approach with Elkington’s Triple Bottom Line and Beck’s Risk Society Theory. Findings show CSR efforts focus on environmental and social responsibilities. Environmentally, VDNI Inc. employs Electrostatic Precipitator (ESP), Continuous Emission Monitoring System (CEMS), and sparing technology, but only ESP and sparing are in use. Poor dust management has led to black dust pollution, increasing acute respiratory infections. Socially, CSR prioritizes infrastructure, including water distribution, road and bridge repairs, and school renovations, yet lacks community empowerment and public health programs. Water supply remains unequal—Morosi Village receives clean water, while Puuruy Village relies on murky water, causing skin diseases. Overall, VDNI Inc.’s CSR efforts remain insufficient in ensuring environmental sustainability and equitable social welfare.